THE INVESTIGATION OF POLY LACTIC ACID /WHEAT STRAW FIBERS TREATED WITH SILANE COMPOSITES - Mehdi Kalagar (Regional Information Center for Science and Technology (RICeST), 2015)
In this paper, poly lactic acid (PLA)/ wheat straw fibers manufactured by twin screw extruder and molding compression have been studied. Wheat straw fibers were treated with trietoxymethel silane for better compatibility between two phases. Physical properties, tensile properties of the composites were analysis. The effect of the wheat straw fibers on the thermal properties of PLA has also been investigated in DSC experiments. The effects of silane treatment on the wheat straw fibers have been analyzed by FTIR. Scanning electron microscopy from samples surface were used for better study of water absorption and thickness swelling. Composites wheat straw fiber were treated shows signification lower water absorption and thickness swelling than composites PLA/ untreated wheat straw fibers. The lower amount of water absorption and thickness swelling occurred in the pure PLA. The existence crack and break occurred in the surface of PLA/ untreated wheat straw fibers composites after immersion in the water indicating higher water absorption and thickness swelling were in these samples. Wheat straw fibers were treated with silane due to better wetting and better linkage in the interfacial surface with PLA matrix showed higher tensile properties then PLA/ untreated wheat straw fiber composites. Differential scanning calorimeter test showed that with addition wheat straw fibers were treated to pure PLA the increased glass transition temperatures. The nucleating effect of wheat straw fibers, special treatment with silane cause to increased in the crystallization temperature composites than pure PLA which a positive effect showed on the degree of crystallization.